Role of plasmacytoid dendritic cells in breast cancer bone dissemination - Sawant, Anandi (Landes Bioscience, 2013)
Elevated levels of plasmacytoid dendritic cells (pDC) have been observed as breast cancer disseminates to the bone. The selective depletion of pDC in mice led to a total abrogation of bone metastasis as well as to an increase in T(H)1 antitumor response, suggesting that pDC may be considered as a potential therapeutic target for metastatic breast cancer.